2020
DOI: 10.1590/1807-3107bor-2020.vol34.0108
|View full text |Cite
|
Sign up to set email alerts
|

Presence of langerhans cells, regulatory T cells (Treg) and mast cells in asymptomatic apical periodontitis

Abstract: Asymptomatic Apical Periodontitis is essentially an inflammatory disease of microbial aetiology. Association and function of the cell components involved, or specific inductive factors and growth mediators associated with development, maintenance and resolution of the periapical lesions are still unknown. The objective of this study was to evaluate the concentration of Regulatory T cells (FoxP3+; Treg), Langerhans cells (CD1a+; LC) and mast cells in asymptomatic apical periodontitis. 73 cases were selected: 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 38 publications
0
14
2
8
Order By: Relevance
“…When a mast cell becomes degranulated/activated, the secretory granules release tryptases along with other extracellular matrix mediators [ 13 ]. Mast cells are said to play a pivotal role in the pathogenesis and progression of periapical lesions, especially in PCs, leading to their expansion, resorption of bone, vasodilatation and angiogenesis, an inflammatory cell response, and increased content of cystic fluid [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…When a mast cell becomes degranulated/activated, the secretory granules release tryptases along with other extracellular matrix mediators [ 13 ]. Mast cells are said to play a pivotal role in the pathogenesis and progression of periapical lesions, especially in PCs, leading to their expansion, resorption of bone, vasodilatation and angiogenesis, an inflammatory cell response, and increased content of cystic fluid [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dendritic cells morphology was observed in the middle thirds and on the epithelium surface, whereas the rounded shape was mainly observed in the basal and subepithelial layers 22. A low CD1a+ cell count at the expense of CD68+ cells might be related to the migration of these cells to regional lymph nodes after activation induced by contact with antigens or even by cellular apoptosis after antigen presentation to CD4+ T cells 20. In contrast, in the present study, higher immunoexpression of Langerhans cells was observed in the atrophic epithelium and this immunoexpression showed a positive and significant correlation with TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are responsible for the presentation of antigens to T cells and are extremely important in activating helper T-cell responses (Th1, Th2, Th17) or Treg cells. 20 The numbers of Langerhans cells and Treg cells play an important role in the control of the inflammatory microenvironment in RCs. 21 The dendritic cells morphology was observed in the middle thirds and on the epithelium surface, whereas the rounded shape was mainly observed in the basal and subepithelial layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once stimulated, these cells emit signals for the activation of Treg cells, which play an important role in the modulation of the inflammatory microenvironment of periapical lesions by acting as effector cells of the disease. 22 LCs can reside in epithelial components where they act as a first line of defense against root canal antigens both in the hyperplastic 22 and atrophic epithelium of RCs. In the present study, the cytoplasmic projections of LCs conferred a phenotype of DCs, especially in the mild-moderate inflammatory infiltrate.…”
Section: Discussionmentioning
confidence: 99%